Cost-effectiveness of pharmacological interventions for smoking cessation: A literature review and a decision analytic analysis - Song, F; Raftery, J; Aveyard, P; Hyde, C; Barton, P; Woolacott, N (2002)
To evaluate the relative cost-effectiveness of nicotine replacement therapy (NRT) and bupropion SR for smoking cessation, the authors reviewed published studies and developed a decision analytic model from the UK National Health Services perspective. Irrespective of the methods or assumptions involved, the results of published studies consistently indicated that NRT for smoking cessation is cost-effective. No published studies have evaluated the relative cost-effectiveness of bupropion SR for smoking cessation. The results of the decision analyses indicated that, as compared with advice or counseling alone, the incremental cost per life-years saved is about $1,441-$3,455 for NRT, $920-$2,150 for bupropion SR, and $1,282-$2,836 for NRT plus bupropion SR. The cost-effectiveness of adding NRT and bupropion SR to advice or counseling for smoking cessation is better than many other accepted health care interventions.